Ludicidade no ensino de química: uma estratégia de aprendizagem para pessoas com Transtorno do Espectro Autista - ANJOS, Shamya Cristina de Lima Gomes dos (Instituto Federal do Amapá, 2021)
This research seeks to emphasize the teaching of Chemistry, addressing the content of the Periodic Table with the use of technological resources, in search of an alternative methodology for students with Autism Spectrum Disorders (ASD) as main focus through two applications available in the Play Store, the “Quiz da Tabela Periódica” and “Nome Teste da Tabela Periódica”, this methodology was used for all students in classes where students with TEA are enrolled, so it was not necessary to differentiate between the applied teaching activities, but to group them and socialize them all, facilitating and diversifying the way of teaching. In this way, two questionnaires were applied as a data collection tool. The first diagnostic questionnaire was intended for the students of the two classes of integrated technician of the 1st series of the high school of Food and Computer Networks of the chosen school. The second questionnaire was aimed at the teachers of chemistry of the same school, targeting the survey of the methodology of teaching chemistry used in the room to students with the help of alternative resources and aiming at inclusive teaching. The data were measured with qualitative and quantitative diagnosis, for objective questions graphs were used, and for dissertatives categorized as analysis of discourses, enabling and facilitating the understanding of research. In this way, the results obtained demonstrate how comprehensive the methodology was in both classes, revealing the results achieved by the researcher, being perceptive the influence of technological resources in the students' daily education and contributing to the learning of the Teaching of Chemistry, this research aims to contribute to the improvement of traditional teaching and not to replace it. Aggregating new socializable methodologies for other researchers with the same teaching language, creating a collective knowledge of education.